Influence of different anteversion alignments of a cementless hip stem on primary stability and strain distribution. (December 2020) - Fottner, Andreas; Kistler, Manuel; Woiczinski, Matthias; Thorwächter, Christoph; Schmidutz, Tobias F.; Jansson, Volkmar; Schmidutz, Florian
Abstract: Background: Stem anteversion in total hip arthroplasty is well known to have a high impact on dislocation, but empirical data regarding the clinical and biomechanical influence is lacking. Therefore, we evaluated the impact of different anteversion alignments on the primary stability and strain distribution of a cementless stem. Methods: The cementless CLS Spotorno stem was implanted in 3 different groups (each group n  = 6, total n  = 21) with different anteversion alignments: reference anteversion (8°), +15° torsion in anteversion (+23°), −15° torsion in retroversion (−7°) using composite femurs (Sawbones). Primary stability was determined by 3-dimensional micromotions using a dynamic loading procedure simulating walking on level ground. Additionally, surface strains were registered before and after stem insertion in the 3 different groups, using one composite femur for each group (total n  = 3). Findings: The micromotion measurements did not show a significant difference between the 3 evaluated alignments. Moreover, determination of the strain distribution did also not reveal an obvious difference. Interpretation: This biomechanical study simulating walking on level ground indicates that there is no considerable influence of stem ante−/retroversion variation (±15°) on the initial stability and strain distribution when evaluating the cementless CLS Spotorno in composite femora. Highlights: A conventional cementless stem was evaluated in different anteversion variations (±15°). 3-dimensional micromotions and surface strain distributions were measured. There was no significant influence of stem anteversion on initial stability and strains.